Survival rate and associated factors affecting pulpectomy treatment outcome in primary teeth - Methaphon Songvejkasem (Wiley, 2021)
Abstract Objectives To evaluate the survival rates of pulpectomized primary teeth treated under general anesthesia (GA) or local anesthesia (LA), and to determine which factors affected tooth survival following pulpectomy. Materials and methods This retrospective study collected data from dental records. Patients under 5 years of age received dental treatment under GA or LA during 2007–2016, with at least one anterior or posterior tooth receiving a pulpectomy, were recruited. Pulpectomy was considered a failure if the tooth required extraction or retreatment due to pulp treatment failure. Survival analysis was used to assess the outcome. The cumulative survival probability was analyzed with the Kaplan–Meier estimator. Cox regression analysis was used to evaluate the associations between tooth survival and possible prognosis factors; sex, age, dental arch (upper/lower), tooth type (anterior/posterior), molar type (first/second molar), molar location (upper/lower molar), root filling material type, restoration type, preoperative radiographic findings and presence of pathologic root resorption. Results Two hundred and twenty‐seven primary teeth were included. At the 5‐year follow‐up, the survival rates of the pulpectomized teeth treated under GA and LA were 81.4% and 87.4%, respectively, which were not significantly different (p ≥ 0.05). A radiolucency on the preoperative radiograph was the only factor associated with tooth extraction or retreatment following pulpectomy, with a hazard ratio of 3.88 (95% CI = 1.29–11.65). Conclusions Pulpectomized primary teeth treated under GA and LA demonstrated high survival rates. Preoperative radiolucency is a possible associated factor that decreases tooth survival following pulpectomy. Why this paper is important Pulpectomy treatment under GA and LA provided high 5‐year cumulative survival rates, which were not significantly different. Pulpectomy treatment in teeth with a preoperative radiolucency were 3.9‐fold as likely to fail as teeth without pathology. Based on our findings, practitioners could apply these findings and discuss with caregivers about the treatment options, outcomes, and prognosis of pulpectomized teeth.